HOW IS WORK LIFE QUALITY AS ATTORNEY? DITINJAU DARI TRANSFORMATIONAL LEADERSHIP: HOW IS WORK LIFE QUALITY AS ATTORNEY? DITINJAU DARI TRANSFORMATIONAL LEADERSHIP - Novita Samosir (unprimdn.ac.id, 2020)
The ideal leader is a person able to inspire his followers to put the goodness of the organization ahead of personal interests and give special influence to them as to improve their work life quality work lives. Thus,the intention of this study was to determine the correlation among transformative leadership and quality work of life. Subjects in this study were prosecutors at High Court of North Sumatera as many as 105 prosecutors selected with purposive sampling method. Data were altained by transformational leadership and work life quality scale then an analysis test consist of normality distribution and linearity test for colleration were conducted. Product Moment Correlation technique is used as an analysis of the results of research helped by SPSS. The analysis result revealed that the correlation coefficient was 0.625 and p = 0.000 (p <0.05). This indicates that a positive relation exists amongst transformative leadership and quality work of life. These calculation results conceal that the contribution given by transformational leadership to quality work of life is 39 percent, while the remaining 61 percent influenced by other aspects. Based on these results, the hypothesis in this study was accepted, means there is a positive correlation among transformational leadership and quality work of life.